Podocin-Green Fluorescence Protein Allows Visualization and Functional Analysis of Podocytes - He, Bing (American Society of Nephrology, 2011)
Podocytes do not remain fully differentiated when cultured, and they are difficult to image in vivo, making the study of podocyte biology challenging. Zebrafish embryos are transparent and develop a single, midline, pronephric glomerulus accessible for imaging and systematic functional analysis. Here, we describe a transgenic zebrafish line that expresses green fluorescence protein (GFP) from the zebrafish podocin promoter. The line recapitulates the endogenous pronephric podocin expression pattern, showing GFP expression exclusively in podocytes starting 2 days postfertilization. Using the podocyte GFP signal as a guide for dissection, we examined the pronephric glomerulus by scanning electron microscopy; the surface ultrastructure exhibited fine, interdigitating podocyte foot processes surrounding glomerular capillaries. To determine whether the GFP signal could serve as a direct readout of developmental abnormalities or injury to the glomerulus, we knocked down the podocyte-associated protein crb2b; this led to a loss of GFP signal. Thus, podocin-GFP zebrafish provide a model for ultrastructural studies and in vivo visualization and functional analysis of glomerular podocytes. This model should also be useful for high-throughput genetic or chemical analysis of glomerular development and function.